ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MENEMPUH PENDIDIKAN PADA PROGRAM STUDI AKUNTANSI POLITEKNIK CALTEX RIAU - Meliza Putriyanti Zifi; Heri Ribut Yuliantoro (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: This research to analyze the factors that influence the decision of the student to study at accounting major in Polytechnic of Caltex Riau. The sample of this reserach are 75 respondents that consist from 60 accounting student 2014 Generation and 15 accounting student 2013 Generation. The data were collected by using questionnaires. The validity of data was tested by implementing construct validity. From the computation result, items from process, cost, social economic background, motivation, facility, reference, location, promotion, reputation, alumnus, product, and character of Polytechnic study was valid. The reability of data was tested by implementing the Cronbach Alpha. The test of hypothesis will used multiple linier regression. The result of the research show that motivation student is the most significant factor influence the decision of student to study at accounting major in Polytechnic of Caltex Riau. This indication that subject of motivation necessary to make decision to study in Polytechnic of Caltex Riau. Keywords: Student Decision, Education, Process, Cost, Social Economic Background, Motivation, Facility, Reference, Location, Promotion, Reputation, Alumnus, Product, and Character Polytechnic.